AlloDerm with Split‐Thickness Skin Graft for Coverage of the Forearm Free Flap Donor Site. (23rd August 2013) - Wester, Jacob L.; Pittman, Amy; Litton, Tyler; Gross, Neil D.; Wax, Mark K.
Abstract : Objectives: A major cause of forearm donor site morbidity after free flap harvest is lack of split‐thickness skin graft (STSG) take. AlloDerm alone has been shown to allow healing of the donor site, albeit prolonged healing. We sought to evaluate the use of STSG with AlloDerm as compared to STSG alone. Methods: Patientswho underwent fasciocutaneous free flap harvest and had composite grafting at the donor site using AlloDerm+STSG were identified at an academic medical center from 2011‐2012. 166 patients with a STSG alone acted as a control group. Morbidity data and aesthetic results were collected. Results: Eighty patients (50M, 30F) received AlloDerm+STSG. Overall donor site morbidity in the AlloDerm+STSG group was 27.5%, compared to 23.5% in the STSG only group, P = 0.53. Complete STSG loss (5% vs. 3%, P = 0.48), tendon exposure (5% vs. 5.4%, P = 1.0), functional impairment (2.5% vs. 1.8%, P = 0.66), infection (8.8% vs. 9.6%, P = 1.0), hematoma/seroma (5% vs. 3.6%, P = 0.73), and paresthesia (1.3% vs. 3.6%, P = 0.43) were not significant. No patients in the AlloDerm+STSG group required a second STSG after complete loss compared to 3 of 5 patients in the STSG only group, P = 0.17. Aesthetic results were superior in the AlloDerm+STSG group as rated by the surgeon (3.5 vs. 2.6, P = 0.03) and patients (3.7 vs. 2.9, P = 0.05) on a scale of 1‐5. Conclusions: Our results suggest that AlloDerm with STSG can provide thicker coverage of the forearm defect after fasciocutaneous free flap harvest and superior cosmetic results. There is no significant difference in other associated morbidity.